The Impact of Gendered Oppression on the Psyche of Female Characters in the Novel The Pakistani Bride by Bapsi Sidwa - Ahmad, Sana; Hammad, Aswad; Akram, Laraib (Pakistan Journal of Humanities and Social Sciences, 2024)
The study aims to explore the impact of gender oppression on the psyche of female characters in the context of the novel “The Pakistani Bride”. Hence, the main objective of this study is to investigate what sort of gender roles are assigned to the female characters in this novel what type of sufferings they are going through in terms of the fulfilment of those assigned roles which ultimately push them into an impulsive and neurotic state of mind. Freud (2016) psychoanalytic model has been applied as the theoretical framework of this study along with (Beauvoir, 1949) feministic approach. However, a particular sample of paragraphs from the particular novel has been drawn by applying the purposive sampling technique. The findings revealed that in the novel The Pakistani Bride, the female characters are being oppressed by patriarchal constraints and have no right to speak. They are being perceived as subordinates, others, and minor species and have been pushed to the periphery of society by male supremacy in nearly every aspect of human existence. The findings also asserted that the inability of women to speak for themselves is a result of patriarchal oppression and gendered roles that have driven women to suppress their urges and become neurotic.